2004
DOI: 10.1002/app.20108
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of superabsorbent resin by ultraviolet photopolymerization

Abstract: Synthesis of superabsorbent resin (SAR) was achieved by a new method, that of direct UV photopolymerization, and in particular the synthesis of a SAR of acrylic acid-potassium acrylate copolymer by UV photopolymerization was investigated. Influences of ratio (mol) of acrylate monomer to acrylic acid monomer, photoinitiators, crosslinking agents, and exposure time of UV light on the water-absorbent properties were investigated. The results showed that the water absorbency (Q) of SAR based on Irgacure 1700 or Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Ruan et al (2004) studied polyacrylate potassium and polyacrylate sodium hydrogels using different photoinitiators in the synthesis. They found that the highest water absorptions were exhibited by hydrogels synthesized with Irgacure 1700 and Irgacure 1800 [ 34 ]. In this work, we utilized Irgacure 1700.…”
Section: Introductionmentioning
confidence: 99%
“…Ruan et al (2004) studied polyacrylate potassium and polyacrylate sodium hydrogels using different photoinitiators in the synthesis. They found that the highest water absorptions were exhibited by hydrogels synthesized with Irgacure 1700 and Irgacure 1800 [ 34 ]. In this work, we utilized Irgacure 1700.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17] Compared with thermal polymerization, UV photopolymerization has many advantages such as simpler technology, it may be carried out at normal temperature, undergoes a very short exposure time, and produces comparatively less pollution. [18][19] In this study, we propose a method of UV photopolymerization for synthesizing AA, AANa, and MACC tricomponent copolymer SHGs. We then report on the investigation of the influence of the pH value responsive behavior of SHG with different monomer content of MACC, and the mol ratio of monomers AANa to AA on distilled water absorbency Q of the SHG.…”
Section: Introductionmentioning
confidence: 99%
“…Polyacrylamide (pAAM), poly(2‐hydroxyethyl methacrylate) (pHEMA), poly(2‐hydroxyethyl acrylate) (pHEA), and poly(2‐methacryloyloxy) trimethyl ammonium (pMAETAC) are known synthetic hydrogel polymers 7, 18, 22, 23. Usually, these polymer hydrogels are synthesized by thermal polymerization including solution polymerization and inverse suspension polymerization 7, 18, 22–25. Photo polymerization is a common method used to synthesize polymers.…”
Section: Introductionmentioning
confidence: 99%